2020
DOI: 10.3389/fchem.2020.592941
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Singlet Oxygen and Cell Death: Location Matters

Abstract: We developed a tool for targeted generation of singlet oxygen using light activation of a genetically encoded fluorogen-activating protein complexed with a unique dye molecule that becomes a potent photosensitizer upon interaction with the protein. By targeting the protein receptor to activate this dye in distinct subcellular locations at consistent per-cell concentrations, we investigated the impact of localized production of singlet oxygen on induction of cell death. We analyzed light dose-dependent cytotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 64 publications
0
20
0
Order By: Relevance
“…As 1 O 2 is an extremely short-lived molecule, and is highly reactive towards electron-rich biomolecules such as unsaturated fatty acids, the effects of the different treatments are restricted to the locality where they are generated. A recent study using chemooptogenetic methods to target photosensitisers to specific subcellular compartments highlighted the differential apoptotic and necrotic outcomes of 1 O 2 localization ( Liang et al., 2020 ). In Arabidopsis, we previously showed that RB and AO localizes 1 O 2 production to the plasma membrane and vacuole respectively.…”
Section: Introductionmentioning
confidence: 99%
“…As 1 O 2 is an extremely short-lived molecule, and is highly reactive towards electron-rich biomolecules such as unsaturated fatty acids, the effects of the different treatments are restricted to the locality where they are generated. A recent study using chemooptogenetic methods to target photosensitisers to specific subcellular compartments highlighted the differential apoptotic and necrotic outcomes of 1 O 2 localization ( Liang et al., 2020 ). In Arabidopsis, we previously showed that RB and AO localizes 1 O 2 production to the plasma membrane and vacuole respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we show that irradiation of fluorescein solutions leads to the production of 1 O 2 and CO, which affects cell viability, metabolism, and proliferation. Incubation of cells with either fluorescein or FDA enabled us to observe the biological consequences of the extra-or intracellular release of fluorescein photoproducts, especially 1 O 2 , whose short half-life limits its reactivity to the vicinity of its formation [53]. On the other hand, the long half-life of CO allows the molecule to freely pass through biological membranes, to reach dynamic equilibrium, and to affect cells regardless of its production site [44].…”
Section: Discussionmentioning
confidence: 99%
“…These complexes have received a great deal of focus in the past decades for their application both as diagnostic and therapeutic agents. The latter application can exploit photoactivated ligand exchange reactions as well as photo-generation of toxic reactive oxygen species such as 1 O 2 within cells [84]. A second class of metal-based luminophores is represented by complexes of Pt(II), Au(III) and Au(I) [85][86][87][88][89].…”
Section: Discussionmentioning
confidence: 99%